VD_FINDINFO Décision / 2014 / 133 vom 14. Februar 2014 - VD Tribunal cantonal (2014)
RISQUE DE RÉCIDIVE, DÉTENTION PROVISOIRE, PROPORTIONNALITÉ, SOUPÇON | 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH)